Resposta :
Resposta:
letra C
Explicação passo a passo:
Δ = (3)² - 4.1.(-10) = 9 + 40 = 49
X = (-3+/-[tex]\sqrt{49}[/tex])/2
X1 = (-3 - 7)/2 = -10/2 = -5
X2 = (-3 + 7)/2 = 4/2 = 2
X1 - X2 = -5 - 2 = -7
(X1-X2)² = 7² = 49
1/(X1-X2)² = 1/49
Resposta:
1 / 49
Explicação passo a passo:
Para descobrir as raízes sem usar a fórmula de Bháskara, use as relações de Girard, que dizem:
x1 + x2 = -b / a
x1 . x2 = c / a
x1 + x2 = -3 / 1 = -3
x1 . x2 = -10 / 1 = -10
x1 = - 5 e x2 = 2
Logo:
1 / (-5 - 2)²
1 / (-7)²
1 / 49